Proyecto de generacion y transferencia de tecnologia en sistemas de produccion - Ipiales, Colombia: informe de progreso - Pena V., L.A. (International Center for Tropical Agriculture, 1987)
The objectives and methodology used in the project on technology generation and transfer in production systems, currently being carried out in Potosi, Puerres, and Cordoba (Narino, Colombia), are described. On the basis of a survey, the most important aspects of the production systems used by the growers were defined. The maize-bean association is a priority in the 3 localities. (CIAT)